MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI PEWARISAN SIFAT PADA MAHLUK HIDUP DENGAN ALAT PERAGA PLASTIK MIKA - Achmad Alim Asriadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
IMPROVING STUDENT ACTIVITY AND LEARNING OUTCOMES IN INHERITANCE MATERIALS IN LIVING INTERESTS WITH MICA PLASTIC TOOLSThis study aims to determine the increase in student activity and learning outcomes, describe the process of increasing student activity and learning outcomes, and measure the magnitude of the increase in activity and learning outcomes in inheritance material in living things. The use of plastic mica props in class IXC SMP Negeri 8 Bogor City Semester 1 of the 2019/2020 school year. This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The results of this study indicate that using plastic mica props can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using the plastic mica props, the learning outcomes of students only reached an average value of 68.18 then an increase occurred after using the mica plastic props to 85.15 in cycle 1 and 90.15 in cycle 2. So it can be concluded that the use of props mica plastic is very popular with students and there is an increase in student learning outcomes. Therefore, researchers suggest that the use of plastic mica props be socialized and used as an alternative in science learning in schools